2012
DOI: 10.1177/0194599812438041
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Performance of Cochlear Implants in Postlingually Deafened Adults

Abstract: In this study, postlingually deafened adults required about 6 months to learn how to process the artificial signals delivered by the cochlear implant. After this learning phase, the hearing performance entered a stable plateau phase for more than 20 years. This stability reveals the long-term reliability of the technology and the biological stability of the electrode-nerve interface over years. In this study, the authors also evaluated the "ceiling effect" with 5 standard German speech tests, used for evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
97
1
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(112 citation statements)
references
References 17 publications
10
97
1
4
Order By: Relevance
“…The large range of CI outcomes that we observed, as well as the mean performance, is consistent with previous reports from large-scale, international studies (13)(14)(15), indicating that the CI outcomes observed in the present study may be considered representative of the wider CI population.…”
Section: Resultssupporting
confidence: 92%
“…The large range of CI outcomes that we observed, as well as the mean performance, is consistent with previous reports from large-scale, international studies (13)(14)(15), indicating that the CI outcomes observed in the present study may be considered representative of the wider CI population.…”
Section: Resultssupporting
confidence: 92%
“…In some of the studies on CI recipients, ceiling was considered the highest score on a test, that is 100% (Gifford et al, 2008, Lenarz et al, 2012, whilst others used a cut-off of 95% (Helms et al, 2004).…”
Section: Ceiling Definitionmentioning
confidence: 99%
“…This, in turn, has resulted in improved speech perception skills of the recipients (Fabry et al, 2009, Gifford et al, 2008, Lenarz et al, 2012, Ruffin et al, 2007, Gifford et al, 2010. In clinical settings, speech perception outcomes are used to identify the potential candidates for CI surgery and also to evaluate the progress of the CI recipient post implantation (Gifford et al, 2008, Alkaf and Firszt, 2007, Gifford et al, 2010, Dowell et al, 2004, Blamey et al, 1992.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations